“PENGARUH BAURAN PEMASARAN, KUALITAS PELAYANAN, DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN YANG DIMEDIASI REPUTASI PERUSAHAAN DAN PERSEPSI PERUSAHAAN” (STUDI KASUS PADA PT. NAWAKARA BANGUN NUSANTARA) - Hani, Dymitri; Salim, Fahruddin; Rachbini, Widarto (SEKOLAH PASCASARJANA PRESS, 2022)
This study aims to analyze the Effect of Marketing Mix, Service Quality, and Customer Value on Customer Satisfaction Mediated by Company Reputation and Company Perception (Case Study at PT. Nawakara Bangun Nusantara). The research population is the customers of PT. Nawakara Bangun Nusantara totaled 76 customers. This type of quantitative research using a questionnaire. Methods of data analysis using Structural Equation Modeling (SEM) Partial Least Square (PLS).